Unraveling the molecular components and genetic blueprints of stem cells. (December 2003) - Li, Linheng; Akashi, Koichi
Remarkable progress in stem cell biology research over the past few years has provoked a promise for the future of tissue regeneration and gene therapies; so much so, that the use of stem cells in clinical therapy seemed to be just around the corner. However, we now realize there is still a huge task before us to improve our understanding of the nature of stem cells before utilizing them to benefit human health. Stem cell behavior is determined by specific gene products; thus, unraveling the molecular components and genetic blueprints of stem cells will provide important insight into understanding stem cell properties. Here we summarize the research of various groups using microarray technology and other approaches to determine the gene expression profiles in stem cells, particularly in hematopoietic stem cells (HSCs). These works have, to a certain degree, helped to narrow down the candidate genes predominantly expressed in HSCs, revealed a list of stemness genes, and indirectly demonstrated the wide-open chromatin state of stem cells and, with it, the molecular basis of the multipotentiality of stem cells.